Bridging the Generational Gap: Innovative Arabic Speaking Instructional Models for Alpha Gen Students in Pesantren - Zulfan Syahansyah; Abdurrahman (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This research is motivated by the instructional gap between traditional Arabic curricula in pesantrens and the digital-native cognitive characteristics of Generation Alpha. The primary objective is to formulate a curriculum reconstruction and innovative teaching strategies capable of enhancing students' speaking competence through a hybrid approach. Employing a qualitative case study method, data were gathered through in-depth interviews, observations, and documentation at modern Islamic boarding schools. The findings reveal that traditional instructional models trigger high cognitive loads and linguistic barriers, particularly language anxiety, among students. However, the implementation of the